ANALISIS EFEKTIVITAS PENGELOLAAN PIUTANG PT SUZUKI FINANCE INDONESIA (SFI) PEKANBARU - Lidia Fitriani Fitriani; Sumarno '; Gani Haryana Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Receivables arise because of the system of credit sales. Accounts receivable is an asset that is quite material. Therefore, it is necessary that an effective management of accounts receivable and efficiently so that the amount of funds invested in the accounts in accordance with the level of ability of the company so as not to interrupt the flow of cash. In the end, receivables management implemented the company will look at financial ratios pertaining to receivables acquired. PT Suzuki Finance Indonesia (SFI) Pekanbaru is a leasing company engaged in official financing for the brand Suzuki motorcycle. This study aims to measure how effective the company in managing its resources. The method used is quantitative descriptive analysis method, to get a clearer picture and detailed based on the data and information obtained. The data used is secondary data, sales data of credit, consumer finance data and the data of bad debts of the company. The results showed PT Suzuki Finance Indonesia (SFI) Pekanbaru is still not optimal in managing its accounts receivable. PT SFI Branch Pekanbaru should make improvements or changes to the strategy in collecting accounts receivable in order to collect the receivable is less than the maturity and reduce the amount of bad debts of the company. Keywords: Receivable, management